2021
DOI: 10.3390/su13063443
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of an Integrated Steel Mill Using Primary Manufacturing Data: Actual Environmental Profile

Abstract: The current dependency on steel within modern society causes major environmental pollution, a result of the product’s life cycle phases. Unfortunately, very little data regarding single steel production processes have been found in literature. Therefore, a detailed analysis of impacts categorized in terms of relevance cannot be conducted. In this study, a complete life cycle assessment of steel production in an integrated German steel plant of thyssenkrupp Steel Europe AG, including an assessment of emissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
(77 reference statements)
0
11
0
1
Order By: Relevance
“…For reference, according to [35] producing 1 kg of concrete results in 3.5E−5 g of 𝐶𝐹𝐶-11 𝑒𝑞 , with minor variations based on the process specifications. Similarly, producing 1 kg of steel reportedly gives rise to 4.5E−5 [62] or as little as 1.6E−8 [36] g of 𝐶𝐹𝐶-11 𝑒𝑞 . As a result, when [63] estimated the ODP of several buildings based on their materials alone, the values ranged from 2E−3 up to 1E−2 g 𝐶𝐹𝐶-11 𝑒𝑞 /𝑚 2 for residential ones.…”
Section: Application Of the Simplified Framework: Cgep And Codp Asses...mentioning
confidence: 99%
“…For reference, according to [35] producing 1 kg of concrete results in 3.5E−5 g of 𝐶𝐹𝐶-11 𝑒𝑞 , with minor variations based on the process specifications. Similarly, producing 1 kg of steel reportedly gives rise to 4.5E−5 [62] or as little as 1.6E−8 [36] g of 𝐶𝐹𝐶-11 𝑒𝑞 . As a result, when [63] estimated the ODP of several buildings based on their materials alone, the values ranged from 2E−3 up to 1E−2 g 𝐶𝐹𝐶-11 𝑒𝑞 /𝑚 2 for residential ones.…”
Section: Application Of the Simplified Framework: Cgep And Codp Asses...mentioning
confidence: 99%
“…There is a high demand for concrete production, due to which the CO 2 emissions of the construction industry are responsible for about 7% of the global emissions, similar to the iron and steel industries [8][9][10].…”
mentioning
confidence: 99%
“…For comparison of results obtained from this study with previous studies mentioned in the Introduction section of the article, the values were adjusted for the functional units defined in this study. The functional unit in this study considered steel production as well, for which the footprint of 2.1 kg CO2-eq kg steel -1 was considered [36]. For the five methanol scenarios, the studies of Kang et al [5] and Li et al [6] resulted in slightly higher values of GWI than reported in this study.…”
Section: Comparison With Previous Studiesmentioning
confidence: 64%